Genomic NGFB variation and multiple sclerosis in a case control study - Arning Larissa; Kruse Niels; Akkad Denis A; Gold Ralf; Epplen Jörg T (BMC, 2008)
Abstract Background Nerve growth factor β (NGFB) is involved in cell proliferation and survival, and it is a mediator of the immune response. ProNGF, the precursor protein of NGFB, has been shown to induce cell death via interaction with the p75 neurotrophin receptor. In addition, this neurotrophin is differentially expressed in males and females. Hence NGFB is a good candidate to influence the course of multiple sclerosis (MS), much like in the murine model of experimental autoimmune encephalomyelitis (EAE). Methods Ten single nucleotide polymorphisms (SNPs) were genotyped in the NGFB gene in up to 1120 unrelated MS patients and 869 controls. Expression analyses were performed for selected MS patients in order to elucidate the possible functional relevance of the SNPs. Results Significant association of NGFB variations with MS is evident for two SNPs. NGFB mRNA seems to be expressed in sex- and disease progression-related manner in peripheral blood mononuclear cells. Conclusion NGFB variation and expression levels appear as modulating factors in the development of MS.